1982
DOI: 10.1017/s0260305500002846
|View full text |Cite
|
Sign up to set email alerts
|

Snow Stratigraphic Studies At Dome C, East Antarctica: An Investigation Of Depositional and Diagenetic Processes

Abstract: The increased interest in past climatic changes, as revealed by studies of long ice cores from polar ice sheets, has stressed the need for a better understanding of the development of the stratigraphic record preserved in these cores. This paper presents some results of surface investigations at Dome C (74°30'S, 123°10'E), East Antarctica, carried out in austral summers 1978-79 and 1979-80. An explanation is presented of the snow stratigraphy, in terms of depositional and post-depositional processes, that is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 1 publication
2
28
0
Order By: Relevance
“…A number of other meteorological properties a¡ect physical properties of snow and could therefore in£uence O 2 / N 2 . Winds produce high-density surface snow crusts [28,29]. They also induce convection in the snowpack, leading to water vapor transport and the formation of faceted crystals [30].…”
Section: Relationship Between O 2 /N 2 and Insolationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of other meteorological properties a¡ect physical properties of snow and could therefore in£uence O 2 / N 2 . Winds produce high-density surface snow crusts [28,29]. They also induce convection in the snowpack, leading to water vapor transport and the formation of faceted crystals [30].…”
Section: Relationship Between O 2 /N 2 and Insolationmentioning
confidence: 99%
“…This increase induces sublimation (depth hoar formation), upward migration of water vapor, and its subsequent deposition in colder, shallower snow (e.g., [29]). Depth hoar layers are common features of snow on the Antarctic Plateau [28,37].…”
Section: Variable Insolation and The Surface Metamorphism Of Snowmentioning
confidence: 99%
“…Depth hoar formation, for example, has been seen at Taylor Dome and Dome C (Alley et al 1982;Palais et al 1982;Waddington and Morse 1994). In the ®rn, depth hoar will be isotopically heavier than vapour because of non-equilibrium fractionation during condensation.…”
Section: Possible Mechanisms For High-frequency Deuterium Excess¯uctumentioning
confidence: 99%
“…Snow is transported by the wind before it is permanently added to the underlying snow cover. The snow cover at Dome C is therefore highly influenced by the wind (for example, Palais et al, 1982). A lot of effort has gone into describing the effect of the wind on the surface mass balance and the snow microstructure and stratigraphy (for example, Brun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…During a traverse between Syowa Station and the South Pole, surface density was measured at several stakes and was never found to be less than 210 kg m −3 (Fujiwara and Endo, 1971). Palais et al (1982) made several 3 m snow profiles at Dome C and found a strong stratigraphic layering. Besides visible stratigraphy, gross β-radioactivity and microparticles were used to date the layers.…”
Section: Introductionmentioning
confidence: 99%